A note on the most northerly record of Gervais’ beaked whale from the western North Atlantic Ocean - Moore , Michael J.; Rubinstein, Belinda; Norman, Stephanie A.; Lipscomb , Thomas (J. Cetacean Res. Manage., 2023)
A juvenile male Gervais’ beaked whale (Mesoplodon europaeus) was found dead in Barnstable Harbor, Cape Cod Bay, Massachusetts, USA. It apparently died from a septicaemia, possibly induced by a puncture wound of unknown origin. The previous most northerly stranding for this species in the western North Atlantic ocean was from New York State, USA.